MENTORING SCIENTIFIC WRITING AMONG UNIVERSITY STUDENTS: IMPROVING ACADEMIC LITERACY AND READINESS FOR PUBLICATION - Syed Agung Afandi; Rizki Erdayani (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
The ability to write scientific articles is a key competency in fostering students’ academic literacy and research culture in higher education. However, many students continue to face difficulties in understanding academic writing conventions, developing literature-based arguments, and adhering to publication ethics standards. This community engagement program aims to enhance students’ conceptual understanding and the quality of their scientific writing through a structured scientific article writing mentorship program. The activity was conducted offline at Universitas Islam Negeri Sultan Syarif Kasim Riau and involved 60 students from various academic programs and cohorts. The program employed a participatory mentoring approach, consisting of an initial needs assessment, structured workshops on scientific article writing, and intensive mentoring through a writing clinic model. The evaluation was carried out through participatory observation, comparisons of pre-test and post-test results, and document analysis of students’ article drafts before and after the mentoring process. The results indicate an improvement in students’ conceptual understanding of scientific article writing, significant enhancements in the structure and quality of article drafts, and increased readiness for academic publication. The program also confirms the effectiveness of the writing clinic model as an impactful community engagement strategy for strengthening academic literacy and students’ publication culture. Overall, scientific writing mentorship contributes to empowering the internal academic community and supports the development of higher education oriented toward sustainable research and publication practices.